2019
DOI: 10.16997/srjed.2
|View full text |Cite
|
Sign up to set email alerts
|

From Employment to Employability: Uzbekistan and the Higher Education Skills Agenda

Abstract: This article outlines the origins of employability as a concept related to higher education, and its impact on Uzbek higher education policy. By arguing that the recognition of employability arose out of changes in global employment demands, and is aligned to global theories of human capital, it can be asserted that the topdown Uzbek government driven changes in higher education policy have reinforced the employability agenda. Although it is debatable whether a top-down enforced employability agenda is benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Robles (2012) argued that power skills should simultaneously include both hard skills and soft skills. However, Paterson (2019) suggested that the term power skill is more appropriate than soft skill. Sreehari (2021) agreed with this argument and further argued that the power skills include teamwork, personal accountability, self-awareness, critical thinking, cross-cultural communication and emotional intelligence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Robles (2012) argued that power skills should simultaneously include both hard skills and soft skills. However, Paterson (2019) suggested that the term power skill is more appropriate than soft skill. Sreehari (2021) agreed with this argument and further argued that the power skills include teamwork, personal accountability, self-awareness, critical thinking, cross-cultural communication and emotional intelligence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the state's commitment in managing employment and employability issues is evident through various policy initiatives (Paterson, 2019). These initiatives emphasize the creation of an enabling environment for graduate employability.…”
Section: The Socio-political-economic Aspect Of Graduate Employabilitymentioning
confidence: 99%